The Effect of Service Quality Dimensions on Patient Satisfaction: Quantitative Study of Regional Public Hospital - Amir Mahmud (Manunggal Halim Jaya, 2022)
The purpose of this study was to determine and analyze the effect of service quality consisting of responsiveness, assurance, physical evidence, empathy, and reliability on patient satisfaction at the Lamaddukelleng Hospital, Wajo Regency, and to determine and analyze the dimensions of service quality that dominantly affect customer satisfaction at the Lamaddukelleng Hospital of Wajo regency. This research was conducted at the Lamaddukelleng Hospital, Wajo Regency, with a population and sample of 370 respondent taken by the purposive sampling. Data analysis is descriptive to explain research data and research descriptions while analyzing quantitative data using Linear Regression analysis tools. The results of this study prove that simultaneously the hypothesis that Ho is rejected and H1 is accepted, namely that responsiveness, assurance, physical evidence, empathy, and reliability have a significant positive effect on patient satisfaction at Lamaddukelleng Hospital, Wajo Regency. Responsiveness, assurance, physical evidence, empathy, and reliability have been applied well in achieving customer satisfaction at the Lamaddukelleng Hospital, Wajo Regency. Based on the study's results, it was found that the dimensions of service quality based on physical evidence were the dominant influences on patient satisfaction at the Lamaddukelleng Hospital, Wajo Regency. This means that consumers have understood that perceived satisfaction is determined by providing services that follow the availability of facilities, facilities, and expertise that are applied to consumers.